Fussball. Macht. Politik : interdisziplinäre Perspektiven auf Fussball und Gesellschaft - Bens, Jonas; Keinfeld, Susanne; Noack, Karoline, 1961- (Kultur und soziale Praxis., 2014)
This book takes a critical look at the popular sport of football, examining its social, power-political, historical, and mythic structures. Football's entanglements with processes of power and politics are illuminated in various case studies through contributions from highly diverse perspectives: cultural anthropology, history (Mayan and Incan), politics, journalism, communication studies, gender studies, sports science, economics, and sociology. A worthwhile reading for not only football fans but also anyone with enthusiasm for unusual perspectives and surprising insights into history and the present.